REPRESENTATIVE MORAL MESSAGE OF MARJAN ADVERTISEMENT RAMADAN 2023 EDITION FOR THE COMMUNITY - Syafruddin Pohan; Shafira Triana Putri; Misiyem (Media Inovasi Pendidikan dan Publikasi, 2023)
Advertising is a useful place to insert various messages that you want to convey to the public. As the holy month of Ramadan approaches, television media advertisements will begin to enliven this important month for the Islamic religious community, one of which is Marjan's advertisement. Marjan advertisements that are broadcast on television media and Youtube advertisements are used as a sign or reminder by the public that the holy month of Ramadan is getting closer. Marjan's advertisements always insert important life messages. Based on this, this study aims to analyze the moral message contained in the advertisement for Marjan 1444 H using a qualitative descriptive method with semiotic theory introduced by Roland Barthes regarding denotation, connotation and myth. The data collection method is through observing Marjan's 2023 advertisements, both Part 1 and Part 2, which are broadcast via television broadcasts and can be viewed again through the Youtube application. The results of this study indicate that the 2023 edition of Marjan's advertisement can represent a moral message through the audio and visuals displayed by the advertisement such as the environment will be angry if it is not taken care of, do not litter and help each other and if you work together you will achieve success.